Slovenski dijaki o politiki in ženskah v politiki - Truden Zupančič, Vesna (Družboslovne razprave, 2005)
The inquiring research on non-random quota sample among secondary-school youthin Slovenia (n = 460) indicated gender-related differences with respect to their interest in politics: they differently pay attention to it, and according to this, they differently judge politicians and political activity. The youth mostly have the opinion that they are not enough engaged with politics, and are clearly aware of the fact the that number of women in (Slovenian) politics is undersized. However, the research revealed that in terms of questioning women positions in politics, the youth also exhibit more traditionalist point of view (what is more valid for men), when more factual and less principle-based questions are asked (especially questions concerning determinants of different behaviour of women in politics). It means that traditionalism towards women in politics is still firm among youth (particulary among men) despite their attitude of equal principle.
Keywords: Slovenia; Slovenija; mladina; dijaki; vrednote; politika; politics; woman; ženske; politična angažiranost